Healthcare payment rules and household asset allocation: evidence from China's DRG/DIP reform - Jiyang Li; Rui Pan (Frontiers in Public Health, 2026)
Objective This study examines whether China's diagnosis-related group/diagnosis-intervention packet (DRG/DIP) healthcare payment reform changes household financial asset allocation and explores the institutional and household pathways associated with that response. Methods We link official 2019 and 2021 pilot designations to five waves of the China Family Panel Studies (CFPS) from 2014 to 2022 and estimate a staggered difference-in-differences model with individual and year fixed effects and city-clustered standard errors. Results In the fully adjusted specification, reform is associated with a 0.3952 increase in ln(1+household financial product value) (SE = 0.1301; p < 0.01), equivalent to an approximately 48.5% increase in 1+reported portfolio value. The result is robust to PSM-DID, an inverse hyperbolic sine transformation, exclusion of cross-city movers, and 5,000 city-level placebo permutations. In a pre-trend diagnostic comparing the 2021 cohort with never-treated cities, the 2014, 2016, and 2018 coefficients are jointly indistinguishable from zero [F(3, 64) = 0.442; p = 0.724]. Exploratory two-step tests are consistent with changes in household consumption expenditure, the mode of government intervention, and industrial upgrading; the estimated effect is stronger among households without a spouse, lower-expenditure households, and households with internet access. Conclusion The findings suggest that healthcare payment rules may have household-welfare spillovers by improving the capacity to cope with medical expenditure risk and strengthening household financial resilience. The mechanism results are interpreted as channel-consistent evidence rather than causal mediation.